The Gospel of Mark: a socio-rhetorical commentary - Witherington, Ben (William B. Eerdmans Publishing Company, 2001)
This book offers the first sustained attempt to read the Gospel of Mark both as an ancient biography and as a form of ancient rhetoric. Ben Witherington applies to Mark the socio-rhetorical approach for which he is well known, opening a fresh new perspective on the earliest Gospel.Written when the fledging Christian faith was experiencing a major crisis during the Jewish war, Mark provides us with the first window on how the life and teachings of Jesus were presented to a largely non-Jewish audience.According to Witherington, the structure of Mark demonstrates that this Gospel is biographically focused on the identity of Jesus and the importance of knowing who he is-the Christ, the Son of God. This finding reveals that Christology stood at the heart of the earliest Christians' faith. It also shows how important it was to these earliest Christians to persuade others about the nature of Jesus, both as a historical figure and as the Savior of the world.